The Impact of Brand Personality of Smartphones on Customer Loyalty: Mediating Role of Brand Awareness - Haddad, Shafig (Jordan Journal of Business Administration, 2025)
The objective of the current study is to explore the mediating role of brand awareness of smart iPhone mobiles in the impact of brand personality factors “sincerity, excitement, competence, sophistication and ruggedness” on the loyalty of customers in Jordan. The research uses a quantitative, cross-sectional, descriptive and causal method. Data was collected through an online survey of 392 respondents from three universities in Jordan: The University of Jordan, Princess Sumaya University for Technology and Middle East University. Simple, multiple and hierarchical regression and factor analysis were used to examine the study hypotheses using SPSS 24. Results showed that there is a statistically significant impact of brand personality (excitement, sincerity, sophistication, competence and ruggedness) on customer loyalty. Brand personality (excitement, sincerity and sophistication) has a statistically significant impact on brand awareness, while ruggedness does not affect brand awareness. Results also showed that brand awareness has a statistically significant impact on customers' loyalty, where brand awareness rated highest on effective loyalty, followed by cognitive loyalty and action loyalty. However, brand awareness doesn't have a statistically significant impact on conative loyalty. Lastly, the results showed a strong correlation between brand personality and the loyalty of customers when brand awareness is considered as a mediator.